2022
DOI: 10.1093/mnras/stac2528
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmic Ultraviolet Baryon Survey (CUBS) V: on the thermodynamic properties of the cool circumgalactic medium at z ≲ 1

Abstract: This paper presents a systematic study of the photoionization and thermodynamic properties of the cool circumgalactic medium (CGM) as traced by rest-frame ultraviolet absorption lines around 26 galaxies at redshift z ≲ 1. The study utilizes both high-quality far-ultraviolet and optical spectra of background QSOs and deep galaxy redshift surveys to characterize the gas density, temperature, and pressure of individual absorbing components and to resolve their internal non-thermal motions. The derived gas density… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 94 publications
(109 reference statements)
2
20
0
Order By: Relevance
“…This exercise is entirely independent of the ionization models. The agreement between the temperature determined from the line widths of different elements and the temperature inferred from the best-fit photoionization model (e.g., Qu et al 2022) also provides additional support for the robustness of the photoionization modeling, as well as validation for the assumption of ionization and thermal equilibrium.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…This exercise is entirely independent of the ionization models. The agreement between the temperature determined from the line widths of different elements and the temperature inferred from the best-fit photoionization model (e.g., Qu et al 2022) also provides additional support for the robustness of the photoionization modeling, as well as validation for the assumption of ionization and thermal equilibrium.…”
mentioning
confidence: 54%
“…The dynamic state of the gas is dictated by different feeding and feedback processes and is intimately connected to how galaxies grow and evolve (see, e.g., Faucher-Giguere & Oh 2023, for a review). In particular, the cool CGM with a typical gas density of n H ≈ 0.01 cm −3 and temperature of T ≈ 10 4 K (e.g., Qu et al 2022), a nominal source of fuel for sustaining star formation, has an expected effective mean free path of ∼10 14 cm and kinematic viscosity of ≈10 20 cm 2 s −1 (e.g., Spitzer 1962;Sarazin 1986). For a typical cool cloud of size 100 pc (e.g., Zahedy et al 2021), moving at a speed of 100 km s −1 in galaxy halos (e.g., Huang et al 2021), the Reynolds number associated with the gas flow is large, Re 3 10 7 ~´(see Marchal et al 2021, for cold/warm neutral medium observed in Milky Way high-velocity clouds), showing that the cool CGM clouds should be turbulent (see, e.g., Burkhart 2021, for a recent discussion on the turbulent nature of diffuse ionized gas).…”
Section: Introductionmentioning
confidence: 99%
“…If the [O II] emitting gas is in pressure equilibrium with a hot halo, we can gain insights into its physical conditions. Hydrodynamical simulations predict global pressure equilibrium, although small-scale fluctuations from subsonic turbulence can occur (e.g., van de Voort & Schaye 2012; Gaspari et al 2014), though observational results are mixed (see Werk et al 2014;Stern et al 2016;Zahedy et al 2019;Butsky et al 2020;Qu et al 2022). Adopting the group mass from Section 3 and the generalized Navarro-Frenk-White (NFW) pressure profile from Arnaud et al (2010), we estimate hot halo pressure of P hot /k B ≈ 5 × 10 4 K cm −3 at ≈100 pkpc for the N filament.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption-line observations of the CGM have, for example, revealed that the CGM is a dominant reservoir of baryons on galactic scales and can help explain the deficiency of baryons within the virial radius as inferred from the stellar mass to dark matter mass ratio (Werk et al 2014). Simultaneous measurements of multiple ions provide a valuable window into the turbulent and multiphase nature of the CGM across a broad range of redshifts (e.g., Werk et al 2016;Rudie et al 2019;Qu et al 2022). Furthermore, measuring the column density of these tracer ions can reveal key characteristics of the galaxy formation process.…”
Section: Links To Observations-calculating Ion Fractions Andmentioning
confidence: 99%
“…Thus, TRMLs dictate the fate of cold clouds and play a crucial role in regulating the amount of cold gas that is available for star formation and black hole growth in galaxies. TRMLs are also essential to observations because they host the intermediate-temperature gases that contribute a significant amount of spectral features (see, e.g., Gronke & Oh 2020 on how a significant amount of emission from a cloud comes from TRMLs) commonly seen in both emission (e.g., Hayes et al 2016;Reichardt Chu et al 2022) and absorption (e.g., Werk et al 2014;Qu et al 2022).…”
Section: Introductionmentioning
confidence: 99%